Attitudes of faculty members in Palestinian universities toward employing artificial intelligence applications in higher education: opportunities and challenges - Omar, Amal; Shaqour, Ali Zuhdi; Khlaif, Zuheir N. (Frontiers in Education, 2024)
This study aims to identify the level of attitudes of faculty members in Palestinian universities regarding the opportunities and challenges of employing artificial intelligence applications in higher education. The researchers used a descriptive approach, and the study's sample consisted of (130) faculty members at An-Najah National University. Data was collected using two specific questionnaires, one focused on opportunities and the other on challenges. Data analysis was conducted using statistical tests, specifically calculating means and standard deviations, Independent Samples Test, Mann-Whitney test, One Way ANOVA, and Kruskal-Walli's test. The study's results indicated that the average level of attitudes among faculty members regarding the opportunities and challenges of employing artificial intelligence applications in higher education was high. Furthermore, the results revealed no statistically significant differences in all areas of opportunities and challenges related to gender, except in "supporting learning and teaching processes," which favored males. The results indicated no statistically significant differences in all areas of opportunities and challenges related to the educational qualifications, except for the "Benefits of AI applications in teaching and education," in favor of an associate professor. The results also indicated no statistically significant differences in the opportunities and challenges of employing artificial intelligence applications attributed to variables of years of experience and the college. Based on this, the study recommends the necessity of implementing intensive training programs for university faculty members to enhance their skills in using artificial intelligence applications in higher education, as well as addressing the concerns and risks that hinder the adoption of these applications. Additionally, conducting experimental research to explore the integration of artificial intelligence applications in education and evaluate their effectiveness is essential.